2002
DOI: 10.4116/jaqua.41.35
|View full text |Cite
|
Sign up to set email alerts
|

Eolian Dust Fluctuation during the Past 200,000 Years Revealed from Quartz in North Pacific Deep-sea Sediments.

Abstract: Magnetic susceptibility evidence of monsoon variation on the Loess Plateau of central China during the last 130,000 years. Quat. Res., 36, 26-36.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Nagashima et al [2004] reported that grain size distributions of detrital materials for samples of hemipelagic sediment derived from the northern part of the Japan Sea could be described by the combination of two lognormal distributions of grains with clay‐ and silt‐sizes. Lognormal fitting was preferred for the Japan Sea sediments on the basis of the observation that grain size distribution of aeolian quartz in the North Pacific sediments is close to lognormal distribution [ Okamoto et al , 2002]. This idea is also supported by our own observation on aeolian dust that fell in the northern part of Japan on May 2002 shows grain size distribution close to lognormal distribution [ Nagashima et al , 2007].…”
Section: Resultsmentioning
confidence: 96%
“…Nagashima et al [2004] reported that grain size distributions of detrital materials for samples of hemipelagic sediment derived from the northern part of the Japan Sea could be described by the combination of two lognormal distributions of grains with clay‐ and silt‐sizes. Lognormal fitting was preferred for the Japan Sea sediments on the basis of the observation that grain size distribution of aeolian quartz in the North Pacific sediments is close to lognormal distribution [ Okamoto et al , 2002]. This idea is also supported by our own observation on aeolian dust that fell in the northern part of Japan on May 2002 shows grain size distribution close to lognormal distribution [ Nagashima et al , 2007].…”
Section: Resultsmentioning
confidence: 96%
“…In western China, one of the main dust source areas in the world, eolian dust activity has been linked to seasonal changes in large-scale atmospheric circulation patterns (An et al, 1995;Littmann, 1991). Many investigations of land (An and Porter, 1997;An et al, 1991;Ding et al, 2000;Porter and An, 1995) and ocean (Hovan et al, 1991;Okamoto et al, 2002;Rea and Leinen, 1988) sediments have shown that Asian dust flux in downwind areas is mainly controlled by the aridity in the source areas and by the atmospheric monsoonal circulations in the glacialinterglacial cycles. Their present activity is reported to have strong positive correlation with the surface wind velocity (Kurosaki and Mikami, 2003) and negative correlation with the antecedent summer and annual precipitation and soil moisture anomalies (Liu et al, 2004).…”
Section: Introductionmentioning
confidence: 99%